Perry Bros. Circus : touring Australia for over 100 years. Coming to this town soon. - Perry Bros. Circus ([Australia] : Perry Bros. Circus, 1970)
Poster promoting circus performances. Features blue toned photographs of scenes from the late 1800s, 1920s and c.1980. A brief history of the circus appears in the centre: "The original Perry Bros. Circus was founded over 100 years ago, when the Perry ancestors owned 'The Half-Way Hotel', between Tambo and Blackall in Western Queensland. They eventually exchanged the hotel for a bullock team and so started their circus days ... During the 1930s, Perrys became one of the biggest shows in Australia. They were particularly well known for their High-Jumping horses..."
Caption title.
Vivian James Carter Collection.
National Library of Australia's 2nd copy [POSTER 2023-4779] has stains.
Also available online
Keywords: Perry Bros. Circus -- Posters; Circus -- Australia -- Posters; Circus performers -- Australia -- Posters; Circus animals -- Australia -- Posters; Circus posters -- Australia; Advertising -- Circus -- Australia -- Posters; Amusements -- Australia -- Posters; Performing arts -- Australia -- Posters; Posters, Australian; Australia -- Posters; Australian